The serum sodium level and the severity of liver cirrhosis complications: A cross sectional study in BSMMU, Dhaka, Bangladesh - Islam, Susmita; Ghosh, Chanchal Kumar; Hamid, Rayhan; Shahidullah, Md; Amin, Md Rasul; Rahim Miah, Md Abdur (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Patients with advanced cirrhosis of liver present with clinical manifestations such as intracta- ble ascites, severe hyponatremia, and reduced arterial blood pressure. The purpose of this study was to observe the relationship between serum sodium levels and the severity of complications associated with liver cirrhosis. From April 2019 to September 2020, this cross-sectional study was done at the Department of Gastrenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Total 96 patients with cirrhosis of liver from both sexes in the study were enrolled by using sequential sampling. Patients were divided into Child-pugh classes, and the severity of complications were evaluated. The serum sodium level was tested in all of the patients. The relationships between it and various stages and complications of cirrhosis were statistically investigated. Serum sodium level was decreased significantly from child pugh class A to B to C (p value <0.0001). Patients with severe ascites had lower serum sodium level than mild and moderate ascites (p=0.00). In complications of ascites like refractory ascites, spontaneous bacterial peritonitis and hepatore- nal syndrome, mean sodium level was low (<130 mm0l/L) but there was no significant differ- ence among them(p=.091). Level of serum sodium lowered significantly in hepatic encepha- lopathy of grade III & IV than grade I & II and those with no hepatic encephalopathy (p=0.00). But there was no significant difference of serum sodium level among different grades of esophageal varices (P=0.336). Low serum sodium levels were shown to be linked with greater liver dysfunction and the severity of liver cirrhosis-related complications. BSMMU J 2022; 15(1): 20-24